Aspartame in the Diet: A Contribution to the Debate on Safety and Health Impact - Biernikiewicz, Milena; Biernikiewicz, Julia; Wilewska, Anna; Pomirski, Bartosz; Pomirska, Agata; Borowiec, Agnieszka; Alabrudziński, Konstanty; Borowiec, Kinga; Kwaśniewska, Paulina; Hovsepyan, Artur (Journal of Education, Health and Sport, 2025)
Introduction Global sugar consumption remains at alarmingly high levels, far exceeding World Health Organization recommendations. This raises the question of whether sweeteners, as low-sugar substitutes, can become a key solution to help people switch to healthier alternatives. WHO guidelines suggest limiting free sugars to less than 10% of daily energy intake, with further benefits for reducing it to below 5%. Such changes can improve overall health and reduce the risk of obesity, diabetes, cardiovascular diseases, and cancer. Among many sugar substitutes, aspartame is one of the most widely used synthetic sweeteners. Purpose The purpose of this article is to review the health effects of aspartame, focusing on its safety, cancer risk, impact on metabolism, obesity, diabetes, and other long-term effects. This paper aims to present scientific evidence on aspartame’s safety, including studies supporting its use and those raising concerns. It also discusses potential risks, especially for individuals with phenylketonuria, and provides expert recommendations for its consumption. Conclusion Aspartame, a widely used sugar substitute, has caused controversy due to concerns about its long-term health effects, such as potential cancer and neurodegenerative risks. However, most health organizations consider aspartame safe when consumed in moderation. Despite some studies linking it to health issues, there is insufficient evidence to confirm these risks in humans. People with phenylketonuria should avoid aspartame, but for most, it is safe within recommended daily intake limits. Materials and methods: Our review is based on an analysis of material collected in ’Pubmed’, ’Google Scholar’ and other scientific articles using the keywords: aspartame, aspartame safety, aspartame controversy.